Debating development discourse : institutional and popular perspectives - Eade,Deborah(Editor) Ligteringen,Ernst(Editor) (International political economy series, 1995)
The theory and practice of international 'development' reflect the precipices of crisis the world is currently poised upon. This book critically reflects on the current deadlock in institutional and academic development discourse, and analyses popular resistance to global 'development' strategies imposed by capital and bureaucratic state power.